INTO THE FRONTIERS: THE RELAY SYSTEM AND MING EMPIRE IN THE BORDERLANDS, 1368–1449. (November 2015) - Harris, Lane J.
Abstract : This article examines the myriad ways the relay system 驛傳 (yichuan) facilitated the movement of the Ming empire into the borderlands. As the early Ming emperors understood, an efficient relay system was vital to the movement of Ming armies into the periphery, the exercise of political authority over Han and non-Han populations, the rituals of diplomatic relations with foreign emissaries, and the routine exercise of bureaucratic power over the borderlands. By the early 1420s, early Ming emperors had used the relay system to spread and consolidate imperial control over the traditional Han territories, incorporate new, fragile areas like Guizhou and Yunnan into the Ming polity, and lead colonial invasions into upland Southeast Asia, throughout Đai Viêt, and all the way into the Siberian forests of Nurgan. In the 1430s and 1440s, however, just as the expensive relay system began to experience its own problems, the Ming presence in the borderlands provoked a series of wars in ĐaiViêt, Luchuan, and Mongolia that forced the Ming government to withdraw the relay system out of the imperial margins.